Mechanical Feasibility Analysis of the Surface Microstructure to Be Used in the Nuclear Reactor - Huang, Shan; Yue, Ti; Yuan, Pan; Zhu, Fawen; Wang, Haoyu; Liu, Menglong; Huang, Chunlan; Li, Hua; Li, Yun (Frontiers in Energy Research, 2022)
With the continuous improvement of nuclear reactor power, the use of surface microstructures to enhance the heat exchange between the coolant and the solid surface has become the research focus of many researchers. However, the extreme environment inside the core, especially the continuous impact of the high-velocity liquid on the solid surface, poses a severe challenge to the reliable service of the microstructure. To this end, this paper establishes a numerical calculation method for the droplet scouring the solid wall to analyze and evaluate the mechanical feasibility and reliability of the surface microstructure under the impact of high-speed droplets. First of all, the physical process of the liquid droplet scouring the solid surface was described and analyzed, then the mathematical equations which describe the physical process were built by coupling the key physical parameters of the interface such as displacement and stress. Finally, the internal stress distribution and its change trend with and without the microstructure were obtained. The calculation results show that during the process of a droplet hitting the solid surface, due to the superposition of shock waves inside the droplet, there will be a stress field distribution on the solid side that cannot be ignored. The introduction of the surface microstructure will significantly change the stress field distribution on the solid side. The liquid film formed on the surface of the microstructure has a significant buffering effect on the impact of the droplets, which greatly reduces the stress level in the solid. The maximum stress level in the solid with microstructure is only about 50% of that in the solid without the microstructure. Therefore, it can be judged that the surface microstructure can meet the mechanical performance requirements under the condition of droplet scouring.